Functional and structural features of the retina, fixation characteristics and their correlations with visual acuity in nystagmus and amblyopia of various origins - V. V. Neroev; E. P. Tarutta; R. R. Khubieva; A. V. Apaev (Российский офтальмологический журнал, 2022)
Purpose. To study the parameters of visual fixation, photosensitivity of the retina in the macular region, thickness of the central region of the retina and the choroid and their relationship with the best corrected visual acuity (BCVA) and refraction in nystagmus and various types of amblyopia.Material and methods. 65 patients aged 5 to 44 (mean age 12.61 ± 7.12 years) were divided into 6 groups depending on the type of amblyopia and associated conditions. The control group was composed of subjects of the same age range without eye pathologies. The retinal photosensitivity and fixation parameters were studied using an MP-3 Nidek microperimeter (Japan). Chorioretinal parameters were evaluated using an RS-3000 Advance 2 spectral optical coherence tomograph (Nidek, Japan).Results. Retinal photosensitivity was lower in the groups with nystagmus and relative amblyopia in congenital myopia compared with the control group. The indices of density and stability of fixation were the lowest in nystagmus and dysbinocular amblyopia. In all groups with nystagmus, a smoother profile of the foveal region was revealed as compared to the control group. The grossest violations of the differentiation of the central fossa were found in nystagmus in combination with congenital myopia. In nystagmus, refractive and dysbinocular amblyopia, a significant correlation was found between the indicators of BCVA and the density of fixation. In the groups associated with congenital myopia, a relationship was found between BCVA, refraction, and foveal photosensitivity.Conclusion. With nystagmus, violations of both fixation and photosensitivity are revealed. With relative amblyopia due to congenital myopia, the fixation is normal while photosensitivity is impaired. With dysbinocular and refractive amblyopia, the photosensitivity of the retina remains within the normal range, and the fixation parameters are slightly reduced.